83 Retention of Surgically Mediated Access Improves Vascular Outcome in Transfemoral Tavi. (31st May 2014) - Nadir, Adnan; Khoo, Chee; Sandhu, Kully; Nolan, Jim; Fairhead, Jack; Ehsan, Omer; Arun Pherwani, Mark Gunning
Abstract : Background: The transfemoral approach is the most widely used access route for transcatheter aortic valve implantation (TAVI). Early experience incorporated surgical cutdown and closure. As the equipment size has been reduced from 24 to 16F, many centres have adopted a true percutaneous approach to both cannulation and closure. However, vascular complications are frequent (4–34%) and are associated with significant morbidity and mortality. There are no direct comparisons reported between these two methods. We present data on all patients undergoing transfemoral TAVI in a single tertiary centre where surgical access and closure by a vascular surgeon remains the default approach. Methods: Clinical details of all patients who underwent transfemoral-TAVI in a large tertiary centre between 2009 and 2013 were analysed. All patients underwent CT angiography of the aorta, iliac and femoral arteries in advance of treatment. During every transfemoral-TAVI procedure, a vascular surgeon performed surgical cutdown and identified most suitable site for femoral arterial cannulation. Access was then obtained under direct vision with Seldinger technique and sheath was deployed. At the end of procedure the arteriotomy site was closed surgically. In selected cases planned vascular intervention was performed pre-emptively to facilitate transfemoral-TAVI. Vascular complications were defined according to the Valve Academic Research Consortium criteria and divided into major and minor complications. Results: During the study period, 92 patients (Mean Age 80.03 ± 6. 41, 73% Males) underwent TAVI procedure. In 80% (74/92) of cases a transfemoral TAVI was performed via surgical cutdown while 19% (18/92) underwent transapical TAVI. While the majority of transfemoral procedures 70/74(94%) were performed under general anaesthetic, 4 (6%) patients had only regional anaesthesia. Major vascular complication occurred in 1/74 (1.3%) patients. This involved rupture of the right common iliac induced by pre-dilatation with and 18F dilator. Emergency surgical repair was performed and the patient underwent successful transapical TAVI a month later. There was one (1.3%) minor vascular complication, a small femoral artery pseudoaneurysm which was managed conservatively. In 2/74 cases (3%), the femoral vessels were significantly stenosed and a Dacron conduit was anastomosed to the common iliac vessel via a retroperitoneal approach. The valve treatment was then successfully performed through that conduit. One patient (1.3%) with severe claudication underwent a femoral endarterectomy and reconstruction of that vessel electively as part of the TAVI procedure. Conclusions: Published data suggests that vascular complications remain a major cause of morbidity in patients undergoing TAVI. Our experience demonstrates that retention of a vascular surgeon as an intrinsic member of the TAVI team both minimises vascular complication and also allows alternative access to be explored.